Dominasi Oligarki dan Ketidakhadiran Partai Politik Hijau di Indonesia - Luthfi Hasanal Bolqiah; Riaty Raffiudin (Nakhoda: Jurnal Ilmu Pemerintahan, 2020)
Contemporary, environmental destruction and its impacts in Indonesia still not adequate to transforms to the platform of a political party as it appears in other countries. Studies have used a liberal framework and prosecuting collective consciousness and civic participation to control environmental issues, not the urgency of green political representation. Furthermore, perspectives of constitusionalism and intitutionalism are too idealistic because inattentive to the individuals interests who are profit-oriented. Consequently, this article attempts to analyze the causes of environmental problems and the absence of formal representation of environmental discourse using oligarchy and political representation theory.  Using qualitative descriptive studies with interview methods and literature studies discovered: (1) green political discourse in Indonesia was scaterred all over the election promises by candidates or political parties, (2) the concentration of natural resources is a sustainable source of income for the oligarchs, (3) the absence of green political platform gave room to live and breathe for oligarch agenda, whereas (4) consolidation of green political platform hampered by internal such as the pros and cons of establishing a political party and external factors such as the party system and Engineering Electoral Systems.